2018
DOI: 10.1002/hpja.21
|View full text |Cite
|
Sign up to set email alerts
|

Body image diversity in the media: A content analysis of women's fashion magazines

Abstract: Issue addressed The narrow representation of body image in the media has been linked to body dissatisfaction, particularly among readers of women's fashion magazines. Some countries have made efforts to improve body image diversity in the media and the fashion industry. This has included attempts to regulate minimum body size of models (eg, Israel, France), and the development of codes of practices such as the Australian Industry Code of Conduct on Body Image. However, there is little evidence of whether these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Even with companies who introduced the take-back scheme (in-store recycling), it has been argued that this gave consumers an opportunity to develop a guilt-free consumption attitude (Gould 2017; Stål and Jansson 2017). Issues with body image: the fashion industry has been accused of using thin models (size zero) which lead to negative consequences among a lot of females including eating disorders and poor self-esteem (de Freitas, Jordan, and Hughes 2018). All of these issues become amplified through ultra-fast fashion where companies focus on getting their new designs on the market within a few weeks.…”
Section: The Fashion Industry and Its Effect On People And The Planetmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with companies who introduced the take-back scheme (in-store recycling), it has been argued that this gave consumers an opportunity to develop a guilt-free consumption attitude (Gould 2017; Stål and Jansson 2017). Issues with body image: the fashion industry has been accused of using thin models (size zero) which lead to negative consequences among a lot of females including eating disorders and poor self-esteem (de Freitas, Jordan, and Hughes 2018). All of these issues become amplified through ultra-fast fashion where companies focus on getting their new designs on the market within a few weeks.…”
Section: The Fashion Industry and Its Effect On People And The Planetmentioning
confidence: 99%
“…Issues with body image: the fashion industry has been accused of using thin models (size zero) which lead to negative consequences among a lot of females including eating disorders and poor self-esteem (de Freitas, Jordan, and Hughes 2018).…”
Section: The Fashion Industry and Its Effect On People And The Planetmentioning
confidence: 99%
“…Maintaining a slim and smart figure is one of the more common themes of women's magazines (de Freitas et al, 2018). Good housekeeping also encourages women to lose weight through a healthy diet, special supplements, and exercises to attain a slender body.…”
Section: Construction Of Ideal Appearancementioning
confidence: 99%
“…People often think of these women as being stressed-out individuals willing to sacrifice both their physical and intellectual health for their career. Some studies [ 17 , 18 , 19 ], demonstrated that fashion models have a positive body image and generally do not report more dysfunctional eating behaviors than controls. However, fashion models were on average slightly underweight with significantly lower BMI than controls.…”
Section: Introductionmentioning
confidence: 99%